Non-hyperbolic force-velocity relationship in single muscle fibres - Edman, K. A.; Mulieri, L. A.; Scubon-Mulieri, B. (Acta Physiologica Scandinavica, 1976)
The force-velocity relation has been studied in sixteen single fibres from frog semitendinosus muscle with particular attention to the high-force portion of the curve. The force-velocity curve was hyperbolic except for a reversal of curvature near 80 % measured isometric tension (P0 ). Rectangular hyperbolas fitted (linear, least-squares method) these data well only when values below 0.78 P0 were considered. Extrapolation of these hyperbolas above 0.78 P0 gave predicted isometric tensions (P*0 ) which averaged 32±6% above the measured P0 values. Hill's constants (1.84°C) for these hyperbolas were: a/P*0=0.177±0.021, b = 0.329±0.035 M.L./sec, Vmax=1.91±0.074 M.L./sec. The reversal of curvature persisted when force-velocity data were obtained using: 1 or 60 min response intervals, afterloaded isotonic responses, grid stimulation, electrically induced contractures and bundles of fibres. The reversal of curvature diminished when force-velocity data were obtained from slightly stretched fibres (about 2.3 µm sarcomere length as compared to 2.1 µm in the control). The results indicate that sarcomere length redistributions probably do not account for the non-hyperbolic force-velocity relation. An explanation for the behavior based on the geometry of the contractile filament lattice is discussed.